If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5-3(2-x)=4(2x+1)
We move all terms to the left:
5-3(2-x)-(4(2x+1))=0
We add all the numbers together, and all the variables
-3(-1x+2)-(4(2x+1))+5=0
We multiply parentheses
3x-(4(2x+1))-6+5=0
We calculate terms in parentheses: -(4(2x+1)), so:We add all the numbers together, and all the variables
4(2x+1)
We multiply parentheses
8x+4
Back to the equation:
-(8x+4)
3x-(8x+4)-1=0
We get rid of parentheses
3x-8x-4-1=0
We add all the numbers together, and all the variables
-5x-5=0
We move all terms containing x to the left, all other terms to the right
-5x=5
x=5/-5
x=-1
| 3x•3x-50=-2x•2x+75 | | 3x2-50=-2x2+75 | | 8×-5y=40 | | -4x+2x=-3x+11 | | 4t=60-3t | | -4+2x=-3x+11 | | 7n-3=n+3 | | X^2x-9=0 | | X*2+7x=-12 | | (2x+3)(4x-8)=(7x+1)(4x-8) | | 10x=45−5x | | 100=y+42 | | -4=c/4 | | 7a-2(a-2)=-16 | | 3x+3^x=342 | | 3x+3^x=341 | | (x-47)(x+11)=0 | | X*2-20=x | | 12÷3x=7 | | 14(x-0,5)=6x-35 | | n*2-4n+4=4 | | 8x=6x+28 | | 3^x+2+5*3^x-4*3^x-1=342 | | 4n^2=10 | | X*2=-8+6x | | X+(x+2)+(x+3)=-78 | | (x-1)^4=2 | | F(x)=6x`+3 | | 2(6b+5)=2+4b | | m+4m-4m+7= | | F(x)=6x^+3 | | -3n-1=n-5 |